2017
DOI: 10.1136/svn-2016-000045
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness and stroke: de-stiffening strategy, a therapeutic target for stroke

Abstract: Stroke is the second leading cause of mortality and morbidity worldwide. Early intervention is of great importance in reducing disease burden. Since the conventional risk factors cannot fully account for the pathogenesis of stroke, it is extremely important to detect useful biomarkers of the vascular disorder for appropriate intervention. Arterial stiffness, a newly recognised reliable feature of arterial structure and function, is demonstrated to be associated with stroke onset and serve as an independent pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 103 publications
1
53
0
6
Order By: Relevance
“…Multiple branching patterns of the terminal end of the basilar artery tend to alter the hemodynamics resulting in arterial remodeling secondary to hypertension; this in turn increases arterial rigidity, plaque depositions and atherosclerosis limiting brain perfusion. 21 Atheroma plaques were observed in 16 cases (14%) within the age range of 38-85 years from the current study. Those formed at the formation and termination ends were frequent among age groups of 38-50 and those that spread entirely across the arteries were among individuals with 50 and above years This could imply that atheroma plaques are most likely to commence at the basilar termination and formation points but spread as the person ages.…”
Section: Discussionmentioning
confidence: 47%
“…Multiple branching patterns of the terminal end of the basilar artery tend to alter the hemodynamics resulting in arterial remodeling secondary to hypertension; this in turn increases arterial rigidity, plaque depositions and atherosclerosis limiting brain perfusion. 21 Atheroma plaques were observed in 16 cases (14%) within the age range of 38-85 years from the current study. Those formed at the formation and termination ends were frequent among age groups of 38-50 and those that spread entirely across the arteries were among individuals with 50 and above years This could imply that atheroma plaques are most likely to commence at the basilar termination and formation points but spread as the person ages.…”
Section: Discussionmentioning
confidence: 47%
“…Thus, in previous studies, there was found a relation between PWV and stroke development in hypertension. The increase in PWV by 1 m/s increased all-cause and cardiovascular mortality by 15% [11,13,35].…”
Section: Resultsmentioning
confidence: 99%
“…Increased vascular stiffness being one of the markers of subclinical atherosclerosis is associated with the development of cardiovascular complications (myocardial infarction, stroke, HF, kidney disease, and high rates of overall mortality) [8][9][10][11].…”
mentioning
confidence: 99%
“…These beneficial effects on arterial stiffness are independent of blood pressure lowering effects [52]. These findings suggest that reversibility of arterial stiffness by blood pressure independent effects may also be attributable to local remodeling effects of these drugs on large artery stiffening [62]. A combination of ACE inhibitors and AT-1R antagonists caused significant decrease in PWV in chronic kidney patients [63].…”
Section: Pathological Mechanisms Of Excessive Arterial Stiffnessmentioning
confidence: 99%